Centers in the Event Domain: A Retake on the Wholeness of Urban Spaces - Ridvan Kahraman (Urban Planning, 2023)
This article demonstrates that geometric analysis by itself is not enough to evaluate Alexander’s wholeness in public spaces and that his theories of wholeness can—and should—be extended into the realm of events. The first section provides a summary of the theory of centers and the relevance of events with regard to the theory of wholeness. In the second section, a new way to classify centers is presented, along with insights from Alexander’s works into an approach for incorporating event centers into the theory of wholeness. The final part puts these ideas to the test on a public square in Stuttgart, Germany, using a geometric analysis and an analysis of user activity to determine the performance of the square as a center. The research concludes that utilizing Alexander’s theories from an event-first rather than a geometry-first perspective is an approach especially well-suited for public spaces.